Education Environment as a Preventive Measure Pollution Plastic waste - Asramid Yasin (Postgraduate, University of Mataram, 2026)
Plastic waste pollution is a growing environmental problem, with the consequences of very high plastic use and increasingly severe environmental damage. Public awareness of waste management is also declining. This condition has negative impacts on the environment, such as soil, river, and sea pollution, and threatens human health and ecosystem sustainability. This study aims to analyze the role of environmental education in preventing plastic waste pollution and increasing public awareness of the importance of protecting the environment. This study uses a qualitative approach with a literature review method by collecting data from various scientific journals, books, and research reports. The results of recent studies published in 2020–2024 indicate that environmental education has a significant influence in shaping public knowledge, attitudes, and behavior towards plastic waste management. Education conducted through schools, families, communities, and digital media has been proven to increase public awareness to reduce plastic use, sort waste, and maintain a clean environment. Furthermore, practice-based educational programs are considered more effective in shaping environmentally conscious behavior than purely theoretical approaches. However, the implementation of environmental education still faces various obstacles, such as low community participation, a lack of waste management facilities, and a lack of continuing education programs. Therefore, collaboration between the government, educational institutions, families, and communities is needed to strengthen the educational environment to reduce plastic waste pollution effectively and sustainably.